What drives terrorist innovation? Lessons from black September and Munich 1972 - Silke, Andrew; Filippidou, Anastasia (Springer, 2019)
Understanding terrorist innovation has emerged as a critical research question. Terrorist innovation challenges status quo assumptions about the nature of terrorist threats and emphasises a need for counterterrorism policy and practice to attempt to not simply react to changes in terrorist tactics and strategies but also to try to anticipate them. This study focused on a detailed examination of the 1972 Munich Olympics attack and draws on the wide range of open source accounts available, including from terrorists directly involved but also from among the authorities and victims. Using an analytical framework proposed by Rasmussen and Hafez (Terrorist innovations in weapons of mass effect: preconditions, causes and predictive indicators, The Defense Threat Reduction Agency, Washington, DC, 2010), several key drivers are identified and described, both internal to the group and external to its environment. The study concludes that the innovation shown by Black September was predictable and that Munich represented a profound security failure as much as it did successful terrorist innovation.
Keywords: Terrorism; terrorist innovation; Munich 1972; Black September